Proof of cantor’s continuum hypothesis - J. Kurdics (Journal of Hyperstructures)
We shall attempt to prove Cantor’s General Continuum Hypothesis, a special case of which is known as the Continuum Hypothesis, namely that the cardinality of the power set of an infinite set is the consecutive cardinality. An ordered field of cardinality ℵSρ with interval topology of weight ℵSρ is constructed, where ℵSρ is an uncountable isolated cardinal.